Encapsulation of FePt and FePt3 alloys inside carbon-foam materials. (27th March 2019) - Boi, Filippo S; Wang, Jiayu; He, Yi; Wen, Jiqiu; Wang, Shanling; Zhang, Xi; Yu, Tian; Shi, Lin; Ma, Qiuyan; Lan, Mu; Lei, Li; Xiang, Gang
Abstract: We demonstrate an advanced chemical vapour deposition (CVD) approach in which the addition of Pt-containing hydrocarbons to ferrocene allows the nucleation of a novel carbon-foam material completely filled with elemental Fe and Pt crystal-phases. These phases are then found to alloy into tetragonal FePt and cubic FePt3 in specific annealing conditions. A dependence of the FePt nucleation on the Ar/H2 flow rate is reported. In addition, high pressure (5 GPa) experiments are found to favor the formation of a single FePt3 encapsulated phase together with the nucleation of C–O rich carbon layers in the foam surface.